Social implications of information and communication technology (ICT) in Sankhu, Kathmandu, Nepal - Khatiwada, Lila Kumar; Tolentino, Lutgarda L. (2005)
This paper argues that in a highly stratified society such as Nepal, access to information and communication technology (ICT) creates both positive and negative effects. On the positive side, it improves the community and decision making roles of household members in favor of women. On the negative side, it reinforces existing inequality found in society. This paper reports the results of a study made among 35 households which have been accessing the internet from Sankhu, Kathmandu district of Nepal during 2003. People "with" and "without" access to ICT were described and compared according to gender, caste, age, education and wealth using descriptive statistics. Factors associated with access was analyzed using Probit regression model while Wilcoxon Mann-Whitney test was used to compare the role performance of agricultural, community and decision making activities between "with access" and "without access" households. The Probit regression model showed that the upper caste, higher educated and resource-rich people were more likely to access ICT whereas those who belong to the lower caste could not access this service at all. There was negative relation between age and access to ICT. No significant relation was observed between landholding and access to ICT.
Keywords: Information and communication technologies; Social change